Trueperella pyogenes and Brucella abortus Coinfection in a Dog and a Cat on a Dairy Farm in Egypt with Recurrent Cases of Mastitis and Abortion - Gamal Wareth; Mohamed El-Diasty; Falk Melzer; Jayaseelan Murugaiyan; Amir Abdulmawjood; Lisa D. Sprague; Heinrich Neubauer (Veterinary Medicine International)
Trueperella pyogenes was isolated from a dog and a cat with a mixed infection with Brucella abortus. Both lived on a dairy cattle farm with a history of regular cases of abortion and mastitis. Identification of the bacteria was done by means of MALDI-TOF MS, loop-mediated isothermal amplification (LAMP) based on cpn60, partial 16S rRNA sequencing, and growth on Loeffler Serum Medium. Isolation of Trueperella pyogenes on the dairy farm highlights its neglected role in reproduction failure and draws attention to its effects in the dairy industry in Egypt. Diagnosis and control of abortion in Egypt should include Trueperella pyogenes as one of possible causes of abortion.